Cash-flow shortage as an endogenous bankruptcy reason - Uhrig-Homburg, Marliese (Journal of Banking & Finance, 2005)
This paper develops a simple model for a leveraged firm and endogenizes the firm’s bankruptcy point by assuming that equity issuance is costly. Equity-issuance costs reflect the difficulties in issuing new equity for firms that are close to financial distress. The resulting model captures cash-flow shortage as a reason to go bankrupt, though the equity value is positive. I analyze the optimal bankruptcy point as well as corporate bond prices and yield spreads for various levels of equity-issuance costs in order to study the impact of different liquidity constraints. Finally, I discuss the consequences on optimal capital structure.